Sport psychology practice in Africa: Do culture-specific religion and spirituality matter? - Hagan, John Elvis; Schack, Thomas; Schinke, Robert (Advances in Social Sciences Research Journal, 2019)
Religious and spiritual observances have been found in sport across parts of the world, notably in South and North America, Oceania and Sub-Saharan Africa. This is attributed to the indigenes’ strong religious and /or spiritual belief in the sacred (God or Allah, a supreme deity, and/ or ancestors), who presumably, can turn the course of any life event in ones favour. To date, the potential connections between religion or spirituality and sport from research and applied consultancy perspectives remain uncharted. This conceptual submission reveals a distinction between religion and spirituality based on evidence from religious studies as well as how these could influence cognitive-behavioural practices in sport. These two phenomenological constructs have been shown to provide individuals with psychological resilience in the face of life adversities (e.g., coping) as well as offer other psychological support aimed at athletes’ optimal functioning, performance enhancement and general well-being. To exemplify their manifestation, some peculiar and unique religious and spiritual practices reminiscent of a typical socio-cultural African context are highlighted. We suggest the use of new perspectives such as the athlete-centered and the RRICC models through different approaches (e.g., reflective practice) to facilitate their integration in sport. Future researchers should target the empirical and functional effects of these indigenous religious and spiritual practices through applied work on sport performance related constructs (e.g., flow and peak experiences, counseling interventions) in Sub-Saharan Africa.